2009
DOI: 10.1002/nau.20802
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic effects of silodosin, a new α1A‐adrenoceptor selective antagonist, for the treatment of benign prostatic hyperplasia

Abstract: Silodosin appears to improve detrusor overactivity and obstruction grade in patients with BPH. With silodosin treatment, LUTS could be managed effectively for more than a year in at least 44% of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 27 publications
(43 reference statements)
3
53
0
Order By: Relevance
“…This primary endpoint was considered sufficient to show clinical efficacy. 6,8,12,14,15 To allow patients to make a fair evaluation of the drugs, a crossover design in which patients were treated with both drugs in consecutive 4-week periods, was applied.…”
Section: Discussionmentioning
confidence: 99%
“…This primary endpoint was considered sufficient to show clinical efficacy. 6,8,12,14,15 To allow patients to make a fair evaluation of the drugs, a crossover design in which patients were treated with both drugs in consecutive 4-week periods, was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Silodosin is highly bound to serum proteins, and its displacement from protein binding sites may occur when is coadministrated with other highly protein bound drugs, like VA: this interaction is another mechanism that can lead to the increase of Silodosin serum concentration [29,30] (Figure 4). In our case, we acknowledge that itching skin rash is due to the interaction between VA and Silodosin, since the presentation of the ADR appeared after the introduction of Silodosin and stopped as soon as VA treatment was discontinued, without any recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of these studies showed a significant increase in Qmax, and this was attributed to a particularly high placebo response. However, an open-label study to investigate the urodynamic effects of silodosin in 36 men revealed a statistically significant increase in Qmax after 1 to 12 months of therapy and an improvement in obstruction grade in 56% of men [25]. Maximum cystometric capacity also increased compared to baseline and detrusor overactivity disappeared in 40% of men, with improvement in a further 35%.…”
Section: Emerging Treatmentsmentioning
confidence: 98%